AUDIT LAYANAN SISTEM INFORMASI KEPEGAWAIAN MENGGUNAKAN FRAMEWORK COBIT 5 - Saraswati, Sagung Intan; Pramaita, Nyoman; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro; Vol 21 No 2 (2022): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2022)
SIMPEG – SIMAK DIHAT is Information System of Government Staff that developed by the Denpasar City Personnel and Human Resources Development Agency (BKPSDM) in supporting the implementation of e-government and Denpasar Smart City for the realization of good public services based on "Sewakadharma" as an innovation product. The COVID-19 pandemic has created several changes. Starting from budget efficiency, the Work From Home (WFH) transition, online training and education, have had a huge impact on the development of SIMPEG - SIMAK DIHATI which is a milestone in Denpasar City BKPSDM staffing services. COBIT 5 was chosen because it was considered to be able to describe what should be done in the future development of SIMPEG – SIMAK DIHATI. In addition, COBIT 5 also calculates the capability level value which represents the level of alignment of information technology goals and organizational business goals.